2020
DOI: 10.14740/cr986
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Atrioventricular Block After Valve Replacement in Carcinoid Heart Disease

Abstract: Background: Carcinoid heart disease (CaHD) is a rare condition that has a high impact on the morbidity and mortality of its patients. Once heart failure symptoms develop in the patient with CaHD, cardiac valve surgery is often the only effective treatment. Although atrioventricular block (AVB) is a known postoperative complication of the valve surgery, the incidence of AVB in this population has not been well described. Methods:Comprehensive records were collected retrospectively on consecutive patients with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…784,785 Complications include AV block, requiring pacemaker implantation in 25% of patients. 786 Frequently, the reduced RV function does not improve despite tricuspid valve replacement and HF persists. 787 Thrombus formation on the tricuspid bioprosthesis can occur, especially during the first 3 months post-operatively, and oral anticoagulation with VKA may be considered.…”
Section: Carcinoid Valvular Heart Diseasementioning
confidence: 99%
“…784,785 Complications include AV block, requiring pacemaker implantation in 25% of patients. 786 Frequently, the reduced RV function does not improve despite tricuspid valve replacement and HF persists. 787 Thrombus formation on the tricuspid bioprosthesis can occur, especially during the first 3 months post-operatively, and oral anticoagulation with VKA may be considered.…”
Section: Carcinoid Valvular Heart Diseasementioning
confidence: 99%
“…This is likely explained by the proximity of the tricuspid valve to the AV node, which may often undergo surgical injury or become disrupted due to cardiac tissue edema. One study reported the need for PPM placement in 21-22% of patients who underwent cardiac surgery involving the tricuspid valve [ 6 ]. No definitive guidelines have been published for when a permanent pacemaker (PPM) should be implanted, but current literature generally recommends PPM placement no earlier than 5-7 days from the date of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Pacemaker implantation is safe and can be accomplished with minimal complications. The risk of heart block persists until 6 months after right sided valve surgery; consequently, some authors have recommended prophylactic placement of epicardial leads after surgery [58]. Heart block can rarely occur in the setting of intracardiac metastasis from a carcinoid tumor [59].…”
Section: Treatment Of Arrhythmias In Chdmentioning
confidence: 99%